Paradoxical bleeding and thrombotic episodes of dysprothrombinaemia due to a homozygous Arg382His mutation - Ding, Qiulan; Yang, Likui; Zhao, Xiaoqing; Wu, Wenman; Wang, Xuefeng; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2017)
We have characterised the pathogenic basis of dysprothrombinaemia in a patient exhibiting paradoxical bleeding and thrombotic defects during pregnancy and postpartum. Genetic analysis revealed that the proband is homozygous for the prothrombin Arg382His mutation, possessing only ~1 % clotting activity. The proband experienced severe bleeding episodes during her pregnancy, which required treatment with prothrombin complex concentrates, and then pulmonary embolism and deep-vein thrombosis at 28 days postpartum, which required treatment with LMWH and fresh frozen plasma. Analysis of haemostatic parameters revealed that the subject had elevated FDP and DD and decreased fibrinogen levels, indicating the presence of hyperfibrinolysis. Thrombin generation and clotting assays with the proband’s plasma in the presence of soluble thrombomodulin and tissue-type plasminogen activator indicated a defect in activation of both protein C and thrombin activatable fibrinolysis inhibitor (TAFI). Unlike normal plasma, no TAFI activation could be detected in the patient’s plasma. The expression and characterisation of recombinant prothrombin Arg382His indicated that zymogen activation by prothrombinase was markedly impaired and the activation of protein C and TAFI by thrombin-Arg382His was impaired 600-fold and 2500-fold, respectively. The recombinant thrombin mutant exhibited impaired catalytic activity toward both fibrinogen and PAR1 as determined by clotting and signalling assays. However, the mutant activated factor XI normally in both the absence and presence of polyphosphates. Arg382 is a key residue on (pro)exosite-1 of prothrombin and kinetic analysis of substrate activation suggested that the poor zymogenic activity of the mutant is due to its inability to bind factor Va in the prothrombinase complex.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Prothrombin; protein C; fibrinogen; TAFI; fibrinolysis